Economic Sanctions and Banking Crises in Target Economies. Issue 2 (23rd February 2018) - Hatipoglu, Emre; Peksen, Dursun
Abstract : What effect do economic sanctions have on the stability of banking systems in targeted economies? This manuscript advances the hypothesis that economic sanctions increase the likelihood of systematic banking crises by deteriorating the target economy's macroeconomic conditions and limiting its access to international capital. To test the argument, we gathered data for over 125 emerging economies for the years from 1970 to 2005. The findings indicate that sanctions are likely to raise the probability of banking crises. The results also show that financial sanctions are more detrimental to the stability of banking systems than trade sanctions. Further, we find that the hypothesized effect of sanctions is conditioned by the extent of economic cost inflicted on targeted economies. One major implication of the findings is that sanctions, as external shocks, can potentially destabilize the financial stability of target countries in addition to the well-documented adverse effects on economic growth, political stability, and humanitarian conditions.